Evaluasi Fungsi Regulasi Dinas Kesehatan Provinsi pada Sektor Kesehatan di Provinsi Bengkulu - Adlin Fitri; Laksono Trisnantoro; Dwi Handono Sulistyo (Jurnal Kebijakan Kesehatan Indonesia, 2014)
Background: Government Act Number 38 issued in 2007 on the differentiation of government affairs between central government, local provincial and local district/municipal government stated the obligation of local district/municipal government to protect, serve, empower and ensure the welfare of the community as well as implement regulation in the health sector. Based on data from Bengkulu Provincial Health Office, some health facilities and staff do not register or undertake accreditation and certification. This indicates that regulation function is not yet well implemented. Thus it is necessary to evaluate the regulatory function of provincial health office in the implementation of regulation in the health sector. Objective: To evaluate the regulatory function of Bengkulu Provincial Health Office as a regulator in the health sector, viewed from input, process, output, and environment. Method: The study was qualitative with case study design. Evaluation of function of Bengkulu Provincial Health Office was made on regulation in the health sector, i.e. licensing, registration, accreditation, and certification of health facilities and staff against the standard in the implementation of regulation on licensing, registration and certification. Result: Performance in input for the implementation of regulation was still relatively weak: there was no support of regulation or policy in the implementation of regulation, there was no staff specifically responsible for the implementation of regulation, no budget allocation for regulation function implementation, no standard or method for the implementation of control and supervision, and limited facilities for the operation of regulation. This resulted in poor performance of regulation implementation so that the output was poor, some health facilities and staff were no registered, there was no accreditation and certification. There was no role of the environment, i.e. office of integrated registration service that regulates licensing. Conclusion: the Regulatory function of Bengkulu Provincial Health Office in the health sector was not well implemented due to lack of support from the government as viewed from the input, process, output, and the environment in the implementation of the regulatory function in the area of licensing, registration, accreditation and certification.Latar belakang: Peraturan Pemerintah No. 38/2007 tentang pembagian urusan Pemerintahan antara Pemerintah, Pemerintah Daerah Provinsi dan Pemerintah Daerah Kabupaten/Kota, dimana kewajiban/kewenangan Pemerintah Daerah dalam me- lindungi, melayani, memberdayakan dan mensejahterakan ma- syarakat dan juga peran Pemerintah Daerah melaksanakan regulasi pada sektor kesehatan. Berdasarkan data Dinas Kesehatan Provinsi Bengkulu masih terdapat sarana kesehatan dan tenaga kesehatan yang tidak melakukan registrasi, akre- ditasi dan sertifikasi. Hal ini menunjukkan bahwa pelaksanan fungsi regulasi belum berjalan optimal. Dengan demikian perlu dilakukan evaluasi terhadap fungsi dinas kesehatan provinsi dalam melaksanakan regulasi pada sektor kesehatan. Tujuan Penelitian: Melakukan evaluasi terhadap fungsi regu- lasi Dinas Kesehatan Provinsi Bengkulu sebagai regulator pada sektor kesehatan, dilihat dari input, proses, output dan lingkungan. Metode: Jenis penelitian ini adalah kualitatif dengan rancangan studi kasus, dengan melakukan evaluasi fungsi Dinas Kese- hatan Provinsi Bengkulu dalam melakukan regulasi pada sektor kesehatan yaitu perizinan, registrasi, akreditasi, dan sertifikasi sarana dan tenaga kesehatan dibandingkan dengan standar dalam pelaksanaan regulasi perizinan registrasi, akreditasi dan sertifikasi. Hasil: Kinerja input untuk pelaksanaan regulasi masih sangat lemah yaitu tidak adanya dukungan peraturan atau kebijakan dalam pelaksanaan regulasi, tidak adanya Sumber Daya Manu- sia yang khusus untuk melaksanakan regulasi, tidak ada anggar- an/dana yang dialokasikan untuk pelaksanaan fungsi regulasi, tidak adanya standar atau metode untuk pelaksanaan peng- awasan dan pembinaan, dan keterbatasan fasilitas yang terse- dia untuk operasional kegiatan regulasi. Hal ini menyebabkan proses pelaksanaan regulasi tidak berjalan optimal sehingga output dari pelaksanaan regulasi yaitu masih terdapat sarana dan tenaga kesehatan yang tidak melakukan registrasi, akredi- tasi dan sertifikasi. Dan belum ada peran lingkungan yaitu kantor pelayanan perizinan terpadu dalam regulasi perizinan. Kesimpulan: Fungsi regulasi Dinas Kesehatan Provinsi Beng- kulu pada sektor kesehatan belum dilaksanakan dengan opti- mal karena tidak adanya dukungan pemerintah yang bisa dilihat dari input, proses, output dan lingkungan dalam pelaksanaan fungsi regulasi perizinan, registrasi, akreditasi dan sertifikasi.